Philosophical Thinking in Building Civilized Millennial Humans - Dilla Rafida Rizqya; Ahmad Barizi (Edumaspul: Jurnal Pendidikan, 2024)
Humans are influenced by digitalization in all aspects of their lives; changes in thinking and way of life are inevitable. The emergence of various social media platforms with potentially destructive values ​​is one of the most concerning issues. Thus, philosophy can offer an opportunity for the millennial generation to be an example for civilized people in the struggle against unpleasant irrationality. In this study, the researcher used the Library Research method in his research. By having philosophical thinking, millennials will have better filters in sorting and utilizing digital technology today.